Türkiye'de Yerel Yönetişimin Uygulanabilirliği ve Yerel Gündem 21 Örneği Üzerinden Bir İnceleme - Yıldırım, Arzu (Muş Alparslan Üniversitesi, 2015)
Developments in the world and a rapidly changing economic structures, the need for the emergence of faster and more effective management approach, the center is centrally managed and directives, bureaucratic and cumbersome moving search for a new management approach has led institutions and organizations. This new approach is named governance. This new approach is different from others attempted to align the ruled and governed. The idea is to spread the ring base management scheme is being drawn. You transfer the transfer of authority to local governments, which are closer to the public. The authorization given to the authority given to transparent, transparent, and you can answer that, and not a single institution is included in the non-governmental organizations must be transferred to the city council. This new approach in the public, private and voluntary organizations in a wide range of actors requires them to come together and strive for common goals. In this context, the study will take place primarily stands for governance concept, the concept of governance dimensions, features and tools that focus on local governance, and finally forms the backbone of the research will focus on the applicability of local governance in Turkey

Dünyadaki gelişmeler ve hızla değişen ekonomik yapılar, daha hızlı ve etkili bir yönetim anlayışının ortaya çıkması gerekliliği, merkezden yönetilen ve merkezin verdiği direktiflerle hareket eden bürokratik ve hantal kurumları ve kuruluşları yeni bir yönetim anlayışı arayışına itmiştir. Bu yeni yaklaşım yönetişim diye adlandırılmıştır. Bu yeni yaklaşım diğerlerinden farklı olarak yönetilenler ile yönetenleri aynı hizaya getirmeye çalışmıştır. Yönetim şeması çizilirken halka tabana yayma düşüncesi yer almaktadır. Bunu da halka daha yakın olan yerel yönetimlere yetki devri aktarılmasıyla olur. Yetki verilirken verilen yetkinin saydam, şeffaf ve cevap verebilir olması ve tek bir kuruma değil sivil toplum kuruluşlarının da içerisine dâhil olduğu bir kent konseyine devredilmesi gerekir. Bu yeni yaklaşım kamu, özel ve gönüllü kuruluşlardan çok sayıda aktörün bir araya gelmesi ve ortak amaçlar için uğraş vermelerini öngörür. Bu bağlamda, çalışmada öncelikle yönetişimin kavramsal açılımı gerçekleştirilecek, yönetişim kavramının boyutları, özellikleri ve yerel yönetişim araçları üzerinde durulacak ve son olarak araştırmanın bel kemiğini oluşturan Türkiye’de yerel yönetişimin uygulanabilirliği üzerinde durulacaktır.
anemon
Keywords: governance; local governance; globalization; Local Agenda 21; the city council; yönetişim; yerel yönetişim; küreselleşme; yerel gündem 21; kent konseyi